2021
DOI: 10.3390/su13041749
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dimethyl Carbonate as Alternative Biofuel. Performance and Smoke Emissions of a Diesel Engine Fueled with Diesel/Dimethyl Carbonate/Straight Vegetable Oil Triple Blends

Abstract: Dimethyl carbonate (DMC) is an interesting blending component for diesel fuel (D) owing to the high oxygen content (53 wt.%) and the absence of C–C bonds in its structure. Moreover, DMC can be produced from CO2 and methanol, which provides a renewable way to reduce anthropogenic CO2. This research has been addressed to assess the use of DMC as a solvent of sunflower oil (SO) and castor oil (CO), with the purpose of obtaining biofuels that can replace fossil diesel as much as possible. The blending of DMC with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 42 publications
3
11
0
Order By: Relevance
“…This would be a consequence of the higher energy density of the fuels composed of sunflower oil, which improves the power output of the engine. Also, the lower cetane number of the castor oil blends prolongs the ignition delay, contributing to a higher amount of fuel burned in the premixed combustion phase [34]. In this sense, the results obtained here are consistent with those reported in recent studies [51,55].…”
Section: Brake-specific Fuel Consumption (Bsfc)supporting
confidence: 92%
See 4 more Smart Citations
“…This would be a consequence of the higher energy density of the fuels composed of sunflower oil, which improves the power output of the engine. Also, the lower cetane number of the castor oil blends prolongs the ignition delay, contributing to a higher amount of fuel burned in the premixed combustion phase [34]. In this sense, the results obtained here are consistent with those reported in recent studies [51,55].…”
Section: Brake-specific Fuel Consumption (Bsfc)supporting
confidence: 92%
“…Lee et al observed similar behavior with the addition of 10 and 20% ABE to diesel [53]. This is explained by the high oxygen content in the biofuels, which promotes the oxidation of C, resulting in a better combustion process [29,[32][33][34][35]. Moreover, the low cetane number in the blends, as well as the higher volatility of ABE in comparison to diesel, promote a higher proportion of fuel burning in the premixed combustion phase, which increases the oxidation of the soot particles [53].…”
Section: Soot Emissionsmentioning
confidence: 80%
See 3 more Smart Citations